Multi-layer solar selective absorber coatings based on W/WSiAlNx /WSiAlOyNx/SiAlOx for high temperature applications - Al-Rjoub, A. (2018)
A simulated and an experimental design of multilayer solar selective absorber coatings for high temperature applications is presented in this study. The optical tandem is composed of four layers deposited by magnetron sputtering on stainless steel substrates at room temperature. The first is a back-reflector tungsten layer, that is followed by two absorption layers based on WSiAlNx/ WSiAlOyNx structure for phase interference. The final layer is an antireflection layer of SiAlOx. The design was conducted with the help of SCOUT software creating a multilayer model based on transmittance (T) and reflectance (R) spectra of individual thin layers deposited on glass substrates. The final design shows simultaneously high solar absorptance α=96.0% and low emissivity ε=10.5% (calculated at 400 °C) together with high thermal stability at 450 °C, in air, and 600 °C in vacuum for 400 h and 300 h, respectively.